Effectiveness of Three Doses of mRNA COVID-19 Vaccines in the Hemodialysis Population during the Omicron Period. Issue 4 (2nd April 2023) - Wing, Sara; Thomas, Doneal; Balamchi, Shabnam; Ip, Jane; Naylor, Kyla; Dixon, Stephanie N.; McArthur, Eric; Kwong, Jeffrey C.; Perl, Jeffrey; Atiquzzaman, Mohammad; Yeung, Angie; Yau, Kevin; et al.
Visual Abstract: Abstract : Background: Coronavirus disease 2019 (COVID-19) vaccine effectiveness studies in the hemodialysis population have demonstrated that two doses of mRNA COVID-19 vaccines are effective against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and severe complications when Alpha and Delta were predominant variants of concern. Vaccine effectiveness after a third dose versus two doses for preventing SARS-CoV-2 infection and severe COVID-19 in the hemodialysis population against Omicron is not known. Methods: We conducted a retrospective cohort study in Ontario, Canada, between December 1, 2021, and February 28, 2022, in the maintenance hemodialysis population who had received two versus three doses of mRNA COVID-19 vaccines. COVID-19 vaccination, SARS-CoV-2 infection, and related hospitalization and death were determined from provincial databases. The primary outcome was the first RT-PCR confirmed SARS-CoV-2 infection, and the secondary outcome was a SARS-CoV-2–related severe outcome, defined as either hospitalization or death. Results: A total of 8457 individuals receiving in-center hemodialysis were included. At study initiation, 2334 (28%) individuals received three doses, which increased to 7468 (88%) individuals by the end of the study period. The adjusted hazard ratios (aHR) for SARS-CoV-2 infection (aHR, 0.58; 95% confidence interval [CI], 0.50 to 0.67) and severe outcomes (hospitalization or death) (aHR, 0.40; 95% CI, 0.28 to 0.56) were lower after three versus two doses of mRNA vaccine. Prior infection, independent of vaccine status, was associated with a lower risk of reinfection, with an aHR of 0.44 (95% CI, 0.27 to 0.73). Conclusions: Three-dose mRNA COVID-19 vaccination was associated with lower incidence of SARS-CoV-2 infection and severe SARS-CoV-2–related outcomes during the Omicron period compared with two doses.